Dialectical Behavior Counseling Protocol to Reduce Conduct Disorders in Adolescents - Fidia Ade Fikri; Anandha Putri Rahimsyah; Feida Noorlaila Isti'adah (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
Behavioral disorders in adolescents are psychosocial problems that have a significant impact on personal, social, and academic development. One counseling approach that has been proven effective in dealing with emotional regulation and maladaptive behavior problems is Dialectical Behavior Therapy (DBT). This study aims to develop a DBT counseling protocol based on the profile of conduct disorder levels in adolescents. The research method used a quantitative descriptive approach with 163 junior high school students as subjects. The instrument used was a 28-item conduct disorder questionnaire with a 1–4 Likert scale. Data analysis techniques used percentage analysis and categorization. The results showed that 24.54% of students were in the low category, 61.35% in the moderate category, and 14.11% in the high category. Based on these findings, a DBT counseling protocol was developed, which includes the stages of assessment, counseling contract, implementation of sessions based on core DBT skills, as well as evaluation and follow-up. This protocol is expected to serve as a practical guideline for school counselors in reducing adolescent behavioral disorders in a systematic and structured manner.